Teacher training in physical education: Perspectives of a pedagogical rationality of the body in motion - Abreu, Samara Moura Barreto de (2019)
The purpose of this paper is to discuss the historical-critical divisions in teacher training in Physical Education (PE), as a way that points out perspectives of a pedagogical rationality of the body in motion. It is written as a theoretical-reflexive essay anchored in the foundations of the Critical Paradigm of PE meant by praxis, in which the (mis)leading directions of the professional formation and development reverberate in a reflexive-critical thinking, as a way of acting both culturally and epistemologically. The historical-critical reading of reality in the teaching profession in PE points out as emergent the (re)construction of identity traits in PE about the imperative to be-to do, as opposed to neoliberal hegemonic forces, as a signification of the empowering relations which compose the stage of didactic transformations, glimpsing the process of redemocratization of the pedagogical ideas.